Myelopathy due to copper deficiency: A case series and review of the literature - Peña, Iván; Sarmiento, Juan; Porras, Cristian; Cediel , Ximena; Camargo, Ana (Biomedica, 2023)
Copper deficiency can present as myelopathy by the manifestation of sensory ataxia, secondary to demyelination of the posterior cords of the spinal cord, accompanied by cytopenia, mainly anemia, and leukopenia. Case series study of three patients with myelopathy due to copper deficiency, diagnosed and managed from 2020 to 2022 in a highly complex university hospital in Colombia. Regarding gender, two cases were female patients. The age range was between 57 and 68 years. In all three cases serum copper levels were decreased, and in two of these, different causes of myelopathy affecting the posterior cords of the spinal cord were ruled out, such as vitamin B12, vitamin E and folic acid deficiency, tabes dorsalis, myelopathy due to human immunodeficiency virus, multiple sclerosis and infection by the human lymphotropic virus type I and II, among others. However, at the moment of the myelopathy diagnosis, one patient had vitamin B12 deficiency associated with copper insufficiency. All three cases presented sensory ataxia, and in two, paraparesis was the initial motor deficit. The diagnostic approach must include copper levels assessment in every case of patients with chronic gastrointestinal pathology, chronic diarrhea, malabsorption syndrome, or significant reduction in dietary intake; and the development of neurological symptoms that may suggest cord involvement. It has been reported that a delay in diagnosis can lead to poor neurological outcomes.